USING MANIPULATIVE TEACHING AIDS IN PRIMARY MATHEMATICS: A QUALITATIVE STUDY IN A GRADE 2 CLASSROOM - Avis Amelia Sabillilah; Heru Subrata; Fiena Saadatul Ummah (Jurnal Tatsqif, 2026)
This study examines how manipulative teaching aids were used in Grade 2 mathematics learning at SDN Sidotopo Wetan I Surabaya and how pupils responded to their use. The study was motivated by the difficulty young learners often experience when abstract mathematical ideas are introduced mainly through verbal explanation, textbook exercises, and symbolic procedures. Using a qualitative descriptive design, data were collected through classroom observation, semi-structured interviews with the classroom teacher and pupils, and documentation of lesson materials, pupil work, and classroom activities. The analysis focused on the ways fraction boards, multiplication pouches, and TERKA boards supported pupils’ movement from concrete activity to mathematical representation. The findings suggest that the teaching aids made mathematical ideas more visible and discussable, encouraged participation and peer interaction, and gave the teacher a concrete basis for questioning and guided explanation. However, the value of the aids depended strongly on teacher mediation, especially in modelling, prompting, managing group work, and connecting hands-on activity to mathematical language and symbols. Implementation was constrained by limited availability of teaching aids, uneven teacher confidence in media integration, inadequate classroom facilities, and classroom-management demands. The study concludes that simple, locally available teaching aids can support meaningful lower-primary mathematics learning when they are deliberately selected, carefully facilitated, and connected to clear conceptual goals. The study does not claim measurable achievement gains, but offers a contextual account of how manipulative-based instruction can be strengthened in resource-limited primary classrooms